Successful Mechanical Thrombectomy of Bilateral Middle Cerebral Artery Occlusions Following Apixaban Discontinuation - Bahadar S. Srichawla; Ton Fang; Abigail Bose; Vincent Kipkorir; Annie Ferris (SAGE Publishing, 2023)
Optimal anticoagulation management in patients with atrial fibrillation (AF) during acute ischemic stroke is complex and often poses a significant clinical challenge. An 82-year-old man with AF presented with left-sided hemiparesis and hypoesthesia due to occlusion of the right middle cerebral artery (MCA) after discontinuing apixaban for 5 days. Successful mechanical thrombectomy (MT) achieved thrombolysis in cerebral infarction (TICI) score of 2C. Anticoagulation was postponed due to a small risk of hemorrhagic conversion. However, the patient developed a rare bilateral M1 segment MCA occlusions on the fifth day with a National Institute of Health Stroke Scale (NIHSS) score of 23, leading to an emergent thrombectomy, resulting in TICI 3 and TICI 2C recanalization in left and right MCAs, respectively. The patient required admission to the intensive care unit and was eventually discharged to an inpatient rehabilitation facility with only residual left hemiparesis and moderate dysarthria. This case underscores the delicate balance between the risk of recurrent ischemic stroke and the potential for hemorrhagic conversion when treating anticoagulation in the acute setting. Close monitoring and an individualized approach are necessary for the treatment of patients with AF who have suffered an acute stroke, especially when anticoagulation must be stopped. We encourage future guidelines to incorporate both imaging and clinical data when determining the continuation of anticoagulation in patients with a recent ischemic stroke. This case also depicts the effectiveness of neuroendovascular interventions such as MT to effectively manage rare simultaneous large multi-vessel occlusions with good outcomes.